Sistem Cerdas Pemantauan Pergerakan Bus Wisata Ngulisik Kota Tasikmalaya - Siti Maesaroh; Rudi Hermawan; Dewanto Rosian Adhy; Sutrismawati Lingga Dewi; Akpil Mauhib; Asep Mustopa (LPPM POLITEKNIK LP3I BANDUNG, 2023)
The city of Tasikmalaya has the